2005
DOI: 10.1007/s11103-005-7081-3
|View full text |Cite
|
Sign up to set email alerts
|

Shared molecular characteristics of successfully transformed mitochondrial genomes in Chlamydomonas reinhardtii

Abstract: Three types of respiratory deficient mitochondrial strains have been reported in Chlamydomonas reinhardtii: a deficiency due to (i) two base substitutions causing an amino acid change in the apocytochrome b (COB) gene (i.e., strain named dum-15), (ii) one base deletion in the COXI gene (dum-19), or (iii) a large deletion extending from the left terminus of the genome to somewhere in the COB gene (dum-1, -14, and -16). We found that these respiratory deficient strains of C. reinhardtii can be divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…More than 10 years ago, a mitochondrial mutant deleted for the left telomere and apocytochrome b gene (1.5-kb deletion) was successfully transformed to respiratory competence with partially purified mitochondrial DNA from C. reinhardtii or Chlamydomonas smithii by using a particle-gun device (15). Very recently, the particle gun was also used to transform the same kind of deletion mutant with cloned mitochondrial DNA or PCR constructs (16). In both cases, a wild-type mitochondrial genome replaced the deleted genome after selection of transformants under heterotrophic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 years ago, a mitochondrial mutant deleted for the left telomere and apocytochrome b gene (1.5-kb deletion) was successfully transformed to respiratory competence with partially purified mitochondrial DNA from C. reinhardtii or Chlamydomonas smithii by using a particle-gun device (15). Very recently, the particle gun was also used to transform the same kind of deletion mutant with cloned mitochondrial DNA or PCR constructs (16). In both cases, a wild-type mitochondrial genome replaced the deleted genome after selection of transformants under heterotrophic conditions.…”
mentioning
confidence: 99%
“…Transformation efficiency was low (0.4-5 transformants per microgram of DNA) and did not lead to any genetic manipulation of the mitochondrial genome. Moreover, transformation of point mutants failed, and it was concluded that only mitochondrial genomes deleted for their left end could be transformed (16).…”
mentioning
confidence: 99%
“…The 5.0 kb DNA construct, which contains a wild-type C. reinhardtii COB gene and upstream region was used as starting material (Yamasaki et al, 2005). I-CsmI's target sequence in the 5.0 kb DNA construct was modified using the mega primer method (Sambrook and Russell, 2001).…”
Section: Developing C Reinhardtii Strains Containing Various Single mentioning
confidence: 99%
“…In total, 83 types of single point mutationcontaining 5.0 kb DNA constructs were prepared and ligated into the E. coli vector pT7-Blue (Novagen, Milwaukee, USA). The respiratory deficient C. reinhardtii strain dum-1, which lacks the entire COB gene and the upstream region, was transformed using a mutated 5.0 kb DNA construct to compensate the deleted region as described elsewhere (Yamasaki et al, 2005). After biolistic bombardment of dum-1, the plates were kept in the dark for 3-4 weeks until respiratory-active colonies appeared.…”
Section: Developing C Reinhardtii Strains Containing Various Single mentioning
confidence: 99%
See 1 more Smart Citation